Threads: theory of Vygotsky to learning processes and child development in early childhood education mediated by toy construction - Fábio Tadeu Reina; Luci Regina Muzzeti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article has the objectivity to point out some of the threads of the cultural historical theory of Vygotsky partner to the process of learning and development of children in early childhood education mediated by the construction of toys and games. In this direction, looking to approach the foundations of this theory in order to internalize the reader in his work in search of reflections and readings on the theme proposed here.